Sustainability In Hotel Housekeeping: Green Practices and Operational Efficiency - Setyawan, Aditya Beny; Widagdo, C. Susmono (International Journal of Integrative Sciences, 2024)
This study investigates the execution and consequences of environmentally friendly methods in hotel cleaning, emphasizing their advantages and difficulties. The research findings indicate that implementing environmentally-friendly practices using a qualitative case study technique involving interviews, observations, and document analysis leads to notable improvements in operational efficiency, cost reduction, and guest happiness. Consequently, this boosts the hotel's reputation. Notwithstanding these advantages, there are acknowledged difficulties including substantial upfront expenses, the requirement for extensive personnel instruction, and opposition to altering established practices. Efficient tactics to address these obstacles including enhancing internal communication, establishing alliances with environmentally conscious suppliers, and obtaining robust backing from top-level management. The study asserts that although the process of adopting sustainable housekeeping practices is difficult, the long-term benefits make it a worthwhile investment. However, additional research is necessary to investigate the specific effects and successful implementation tactics in greater detail